Physics for future presidents : the science behind the headlines - Muller, R. (Richard) (New York ; London : W.W. Norton, 2008)
This book explains the science behind the concerns that our nation faces in the immediate future. It outlines the tools of terrorists, the dangers of nuclear power, and the reality of global warming. We live in complicated, dangerous times. They are also hyper-technical times. As citizens who will elect future presidents of the most powerful and influential country in the world, we need to know and truly understand, not just rely on television's talking heads, if Iran's nascent nuclear capability is a genuine threat to the West, if biochemical weapons are likely to be developed by terrorists, if there are viable alternatives to fossil fuels that should be nurtured and supported by the government, if nuclear power should be encouraged, and if global warming is actually happening. Even active readers of serious journalism will be surprised by the lessons that the book contains. It is "must-have" information for all presidents and citizens of the twenty-first century.
I: Terrorism. Nine-eleven ; Terrorist nukes ; The next terrorist attack ; Biological terrorism ; Terrorism : presidential summary -- II: Energy. Key energy surprises ; Solar Power ; The end of oil ; Energy : presidential summary -- III: Nukes. Radioactivity and death ; Radioactive decay ; Nuclear weapons ; Nuclear madness ; Nuclear power ; Nuclear waste ; Controlled fusion ; Nukes : presidential summary -- IV: Space. Space and satellites ; Gravity applications ; Humans in space ; Spying with invisible light ; Space: presidential summary -- V: Global Warming. A brief history of climate ; The greenhouse effect ; A very likely cause ; Evidence ; Nonsolutions ; The fruit on the ground ; New technologies ; Global warming : presidential summary : The buck stops here.
Originally published: 2008.
Includes bibliographical references (pages 347-359) and index.
Keywords: Physics -- Social aspects; Science and state; Science in mass media